Assuring software security against buffer overflow attacks in embedded software development life cycle - Chul Su Park; Jae Hee Lee; Seong Chae Seo; Byung Ki Kim (2010 The 12th International Conference on Advanced Communication Technology (ICACT), 2010)
The Current attack techniques against embedded systems are used more sophisticated. Security has been the subject of intensive research in the area of embedded system. Embedded system developers should consider the security technology which protects, mitigates, and removes the vulnerabilities throughout system development life cycle. This paper is intended to introduce embedded software analyzer to challenges involved in designing secure embedded systems against buffer overflow attacks. We attempt to provide a approach specifying of embedded software security requirements in the analysis phase of SDLC. It provides to understand, analyze, and specify the security requirements at an early phase of the software development.